A solid–liquid hybrid electrolyte for lithium ion batteries enabled by a single-body polymer/indium tin oxide architecture. (10th September 2021) - Kim, Taehoon; Son, Dae-Yong; Ono, Luis K; Jiang, Yan; Qi, Yabing
Abstract: Solid-state electrolytes have received much attention because of their high safety and cycling stability for lithium ion batteries. However, the interfacial contact issue of solid electrolytes with the electrode and active material hinders their practical use. Herein, for the first time, we demonstrate a hybrid electrolyte that combines a solid polyethylene terephthalate (PET) electrolyte with an organic liquid electrolyte to provide synergetic benefits over a single electrolyte. The single-body PET electrolyte/In2 O3 –SnO2 (ITO; 110 nm, 150 nm, 260 nm and 340 nm) electrode was prepared by vacuum sputtering deposition. The simplicity of the electrode composite (e.g., conductive additive-free, solvent-free and binder-free) and its gapless structure between the polymer substrate and the active material significantly impede the formation of by-products from the decomposed electrolyte as well as the growth of an unstable solid electrolyte interphase upon cycling. In addition, the cell configuration of the Li metal/organic electrolyte/PET/ITO electrode enables a process called 'Li + caging', which leaves some of the lithium ions in the PET due to the different ion transfer kinetics of the heteroionic interfaces. The hybrid electrolyte cell not only shows an excellent rate capability at 100–400 mA g −1, but also exhibits high cycling stability (>1200 cycles). Our study lays a cornerstone for the development of practical hybrid electrolytes for lithium ion batteries with improved stability.